Financial Integration with Heterogeneous Beliefs - Jörg Rieger (University of Heidelberg, Department of Economics, 2014)
In this paper we study the effects of financial integration on risk-sharing. Conventional macroeconomic theory suggests that the integration of financial markets improves welfare. In contrast to the literature we assume that households have heterogeneous beliefs. Because of the differences in beliefs, households are not only sharing the risk but also speculating. We show that with speculation, financial integration can increase the risk in the economy and that a full financial integration is not always beneficial. We also have a numerical example for a small set of countries and show that the losses due to heterogeneous beliefs are small.
urn:nbn:de:bsz:16-heidok-170588
Keywords: 330; Heterogeneous Beliefs; Financial Integration; Incomplete Markets